Price attractiveness, distributor relationship, and brand equity impact on customer advocacy in cement industry - Kurniawan, Rahman; Arief, Mts; Abdinagoro, Sri Bramantoro; Heriyati, Pantri (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the role of price attractiveness, distributor relationships, and brand equity in shaping customer advocacy in Indonesia’s bagged cement industry. This verification study focuses on cement retailers as the observation unit. The collection of data uses a questionnaire employing a 5-point Likert scale. A sample of 300 respondents was selected using stratified random sampling. Structural Equation Modeling (SEM) was used for causality analysis. The findings indicate that price attractiveness significantly affects both brand equity and customer advocacy. Distributor relationships strongly influence customer advocacy but have no direct effect on brand equity. Brand equity significantly drives customer advocacy, while price attractiveness indirectly impacts advocacy through brand equity. The study highlights the dominant role of distributor relationships in fostering advocacy, emphasizing trust, reliability, and communication. Based on the findings, strengthening distributor relationships is crucial for the management of cement distributors to enhance advocacy in cement sales. Managers should improve communication, reliability, and trust. Future research can explore additional factors influencing distributor relationships and customer advocacy in commodity markets.